Visualização por meio de mapas como recurso para a democratização dos dados e para a apropriação social da informação - Py, Hesley da Silva (2019)
The goal of this work is to evaluate how the concepts of visualization through maps and participation act as mechanisms for favoring the democratization of data and the social appropriation of information. The context is a society in which information increasingly occupies a central space and where platforms for the dissemination of open data multiply. The motivation is related to the fact that, in a reality fragmented by economic, social and cultural differences, the publication of data in this format, by itself, does not guarantee its use throughout society. On the contrary, insofar as it requires individuals with more technical skills, the provision of access to open data only contributes to the maintenance and aggravation of a model in which those with more resources have an advantage over those who do not. For ensuring more egalitarian conditions so that data and information, especially those acquired or produced with public resources, do not become a factor of exclusion or distinction that this work proposes the insertion into public platforms of the concepts presented above. The adequacy of the concepts was evaluated based on a bibliographical review and semi-structured research, with a qualitative approach, from the managers' perception of the main Brazilian inter institutional platforms that publish data in open formats and of three institutional infrastructures. The results of the bibliographic review presented a series of indications of the competences of the concepts approached for the democratization of the data and for the appropriation of the information. Subsequently, the results of the research with the managers validated what had already been identified in the bibliographic review and added elements that allow, partially, validating the hypotheses proposed for the work. Specifically with respect to the characteristics of the data visualization through the maps, its competence in favor of the data democratization and social appropriation of information is confirmed. The visualization of the data in the maps helps to identify characteristics that can not be observed by reading a table or an alphanumeric file, brings the citizen closer to the data and eliminates the need for complex tools for its use. Regarding the visualization of the information, it is observed that if it is applied unidirectionally, without the possibility of a controversial view, it is characterized as ready information, not collaborating for the democratization of the data nor for the social appropriation of the information. However, if the participation of individuals with different profiles and perspectives is possible, interacting with the visualization of the information, the characteristics of such participation allow us to confirm the hypothesis that such participation diminishes the influences of the author of the initial visualization, presents new perspectives on information, raises the controversy and favors the social appropriation of information.